2023
DOI: 10.1007/s40279-022-01797-7
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Multi-Component Exercise-Based Injury Prevention Programs on Injury Risk Among Footballers of All Age Groups: A Systematic Review and Meta-analysis

Abstract: Background Playing football is associated with a high risk of injury. Injury prevention is a priority as injuries not only negatively impact health but also potentially performance. Various multi-component exercise-based injury prevention programs for football players have been examined in studies. Objective We aimed to investigate the efficacy of multi-component exercise-based injury prevention programs among footballers of all age groups in comparison to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…Emery et al's study showed protective effects for all injuries (RR = 0.30, 95% CI, 0.19-0.49), lower limb injuries (RR = 0.31, 95% CI, 0.19-0.51), ankle sprains (RR = 0.27, 95% CI, 0.15-0.50), and knee twists (RR = 0.36, 95% CI, 0.13-0.98). Emery et al's randomized control trial showed that adolescents who underwent 12 weeks of high-intensity NMT signi cantly reduced sports and muscle injury risks compared to the control group, with an RR of 0.82 (95% CI 0.71-0.94; 95% CI 0.58-1.15), though the effectiveness was not signi cant [24]. Rahnema et al's quasi-experimental study found signi cant correlations between improvements in balance and agility following 8 weeks of regular training and thrice-weekly core stability training among professional speed skaters (p < 0.05), indicating a positive impact on dynamic balance and agility [37,38].…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
“…Emery et al's study showed protective effects for all injuries (RR = 0.30, 95% CI, 0.19-0.49), lower limb injuries (RR = 0.31, 95% CI, 0.19-0.51), ankle sprains (RR = 0.27, 95% CI, 0.15-0.50), and knee twists (RR = 0.36, 95% CI, 0.13-0.98). Emery et al's randomized control trial showed that adolescents who underwent 12 weeks of high-intensity NMT signi cantly reduced sports and muscle injury risks compared to the control group, with an RR of 0.82 (95% CI 0.71-0.94; 95% CI 0.58-1.15), though the effectiveness was not signi cant [24]. Rahnema et al's quasi-experimental study found signi cant correlations between improvements in balance and agility following 8 weeks of regular training and thrice-weekly core stability training among professional speed skaters (p < 0.05), indicating a positive impact on dynamic balance and agility [37,38].…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
“…Most of the described programs focus on preventing injuries in a specific body part like the ankle 3 or the knee 4 . A growing body of evidence suggests that multi‐component programs, that is, programs that target multiple body parts, may benefit the health of youth athletes by reducing the risk of injury 5 . The scarcity of volleyball‐specific injury prevention programs urged the Dutch Volleyball Association (Nevobo) and the Dutch Consumer Safety Institute (VeiligheidNL) to join forces to develop a volleyball‐specific injury prevention program called “VolleyVeilig” using the principles of Intervention Mapping 6 …”
Section: Introductionmentioning
confidence: 99%
“…4 A growing body of evidence suggests that multi-component programs, that is, programs that target multiple body parts, may benefit the health of youth athletes by reducing the risk of injury. 5 The scarcity of volleyball-specific injury prevention programs urged the Dutch Volleyball Association (Nevobo) and the Dutch Consumer Safety Institute (VeiligheidNL) to join forces to develop a volleyball-specific injury prevention program called "VolleyVeilig" using the principles of Intervention Mapping. 6 The VolleyVeilig program was first developed for players 16 years and older to be used during the warm-up phase and consists of more than 50 distinct exercises.…”
mentioning
confidence: 99%
“…Several meta-analyses supported the efficacy of IPPs 19–21. A more cautious interpretation of their efficacy emerged recently when other meta-analyses included the calculation of prediction intervals 22 23. Despite available evidence of their efficacy,9–14 16–18 24–26 and the importance of good compliance for injury reduction,27–29 many studies highlighted a low programme compliance 15 30 31.…”
Section: Introductionmentioning
confidence: 99%